TOWARDS A GLOBAL CURRENCY? CONDITION AND SCENARIOS FOR EVOLUTION OF THE INTERNATIONAL MONETARY ORDER - Jędrzejowska, Karina (Ekonomika, 2014)
The main goal of the paper is to examine the key features of the current international monetary system and provide an overview of scenarios for the future global monetary arrangements. It is noted that just a few years back there seemed to be a bipolar monetary system based on the U.S. dollar and the euro in the making. The rise of China and the possible emergence of the Chinese renminbi as an international currency gave way to a debate on a tripolar monetary system. Today, the future of the international monetary system is still open. It needs reforming in order to meet the requirements of the new global order with multiple growth centers, the growing role of transnational actors, and the increasing global influence of the major emerging economies. The analysis reveals that the relations among the major international currencies are changing, and today at least three scenarios for the future monetary order seem possible. These are the maintenance of the U.S. dollar domination, a shift towards a multipolar currency order, and the gradual regionalization of the currency order. The concept of a single currency – though theoretically attracting – seems impossible to be implemented in the foreseeable future. The analysis is based on monetary and economic theories, historical patterns of the development of monetary regimes, and an extensive literature overview backed by the data provided by the International Monetary Fund (IMF) and the Bank for International Settlements (BIS).